2008
DOI: 10.2807/ese.13.10.08058-en
|View full text |Cite
|
Sign up to set email alerts
|

Asian tiger mosquito (Aedes albopictus) - a threat for Switzerland?

Abstract: The Asian tiger mosquito, Aedes albopictus (Stegomya albopicta) originating from south-east Asia, has spread primarily by the trade of used tyres to the United States, Europe, Latin America and Africa [1]. In Italy, the mosquito species was first detected in Genoa in 1990 and has since spread to several parts of the country, including border areas with Switzerland [2]. In 2000, an active monitoring system was established in southern Switzerland. The first tiger mosquito was detected in the canton of Ticino in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 1 publication
0
22
0
1
Order By: Relevance
“…Ae. albopictus has so far not established itself in Germany, although its ova have been found once (in 2007) in the German Southwest (Pluskota et al 2008) and it has established itself in neighboring Switzerland (Wymann et al 2008). The Netherlands to the West have repeatedly noted the importation of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Ae. albopictus has so far not established itself in Germany, although its ova have been found once (in 2007) in the German Southwest (Pluskota et al 2008) and it has established itself in neighboring Switzerland (Wymann et al 2008). The Netherlands to the West have repeatedly noted the importation of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus established homogenous populations and could be considered as spreading in France, Spain, Croatia, Montenegro, and Slovenia, with Italy being currently by far the most heavily infested country in Europe (European Centre for Disease Prevention and Control [ECDC] 2009). Wymann et al (2008) reported the establishment and onward spread of Ae. albopictus in southern Switzerland, whereas the species was detected but failed to be established in other European countries such as Germany (2007), Belgium (2000), and the Netherlands (2005) (ECDC 2009).…”
mentioning
confidence: 98%
“…Die asiatische Tigermücke, ein potenter Überträger des Chikungunya-Virus, hat sich in den letzten beiden Jahrzehnten in Südeuropa ausgebreitet. Vereinzelte Tigermoskitos wurden bereits nördlich der Alpen gefangen, etwa in der Schweiz, in Holland, in Belgien und in Deutschland im Oberrheintal [45].…”
Section: Infektionen Die Morbidität Zu Verändernunclassified